Analysis of Financial Inclusion and The Number of MSMES To GDP In Indonesia - Teddy Wiranata; Bakhtiar Efendi; Wahyu Indah Sari (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze Financial Inclusion and the Number of MSMEs to GDP (Gross Domestic Product) or Economic Growth in Indonesia. Where there are bound variables, namely work productivity and there are two independent variables, namely financial inclusion and the number of MSMEs. This study uses secondary data by searching for data through the Central Statistics Agency (BPS) Website and the World Bank Website. The data analysis model in this study uses multiple linear regression. The results of the study show that the variables of Financial Inclusion and the Number of MSMEs have a significant effect on GDP (Gross Domestic Product) in Indonesia.